Pentraxin-3: A new parameter in predicting the severity of diabetic foot infection? - Balin, Safak Ozer; Tartar, Ayse Sagmak; Ugur, Kader; Kilinc, Faruk; Telo, Selda; Bal, Ali; Akbulut, Ayhan (Wiley, 2019)
This study was undertaken to evaluate the diagnostic and prognostic values of pentraxin-3 (PTX-3) in patients with infected diabetic foot ulcers (IDFU) as well as to assess the association between PTX-3 levels and IDFU severity. This study included 60 IDFU patients (Group 1), 45 diabetic patients without DFU (Group 2), and 45 healthy controls. Patients with IDFU were divided into mild, moderate, and severe subgroups based on classification of clinical severity. Patients who underwent amputation were also documented. Blood samples were collected to determine PTX-3 levels. PTX-3 levels in healthy controls, Group 1, and Group 2 were 5.83 (3.41-20) ng/mL, 1.47 (0.61-15.13) ng/mL, and 3.26 (0.67-20) ng/mL, respectively. A negative correlation between plasma PTX-3 and glucose levels was found. There were significant differences in terms of procalcitonin (PCT) and PTX-3 levels in the subgroup analysis of Group 1. The PTX-3 level in patients who did or did not undergo amputation was 4.1 (0.8-13.7) and 1 (0.6-15.1) ng/mL, respectively. Results suggest that PTX-3 is a particularly effective marker in patients with IDFU, both in terms of predicting disease severity and assisting in the decision to perform amputation.
Keywords: amputation; diabetic foot ulcers; infection; pentraxin-3